EtCO2 Levels in Medical Students Wearing N95 Masks - Safira Eka Putri Madubun; Ony Wibriyono Angkejaya; Bertha Jean Que; Felmi de Lima; Christiana Rialine Titaley (Jurnal Respirasi, 2023)
Introduction: N95 masks are very popular for daily use and can actively filter microparticles such as viruses. However, there are concerns that prolonged wearing of the mask may result in exhaled CO2 accumulation between the face and the mask, which may cause increased end-tidal carbon dioxide (EtCO2) levels and physiological changes. This study aimed to determine EtCO2 levels in students wearing the N95 mask. Methods: This was an experimental study with a case-control design. The subjects were divided into a treatment and a control group and were subjected to five measurements in 120 minutes. The data were analyzed using the independent samples T-test (normally distributed data) and the Mann-Whitney U test (not normally distributed data). Results: Mann-Whitney test at minute 0 showed that p = 0.010, independent sample T-test at minute 30 showed that the control group p = 0.016, while in the treatment group p = 0.019. Independent sample T-test at minute 60 for the control group p = 0.034, while the treatment group p = 0.037. Independent sample T-test at minute 90 for the control group and treatment p = 0.001, and independent sample T-test showed that at minute 120 in the control and treatment groups p = 0.000. Conclusion: The EtCO2 measurements at each of the five time points showed a statistical difference (p < 0.05). However, medical students who wore an N95 mask did not suffer adverse effects because the EtCO2 values in the control group were higher than in the treatment group.